Bioactive Photodegradable Hydrogel for Cultivation and Retrieval of Embryonic Stem Cells. (18th June 2015) - You, Jungmok; Haque, Amranul; Shin, Dong‐Sik; Son, Kyung Jin; Siltanen, Christian; Revzin, Alexander
Abstract : The development of a novel photodegradable heparin‐based hydrogel for cultivation and retrieval of embryonic stem cells is described. Mouse embryonic stem cells cultured atop the gel with encapsulated growth factors (GFs) express higher levels of differentiation markers compared to a standard protocol employing soluble GFs. Beyond improving differentiation of stem cells, the novel hydrogels can be used to release specific stem cell colonies without disturbing neighboring cells. This way, stem cell colonies can be retrieved at different time points and from different locations of the culture surface for polymerase chain reaction (PCR) analysis without the loss of the microenvironment context. The ability to retrieve some stem cell colonies without disturbing neighboring colonies will open possibilities for characterizing in‐dish heterogeneity of stem cell phenotype and will also allow to conserve cells/reagents. Overall, the bioactive photodegradable hydrogel developed in this study may offer new possibilities for cultivation and analysis of stem cells as well as other cell types. Abstract : A photodegradable bioactive hydrogel helps to improve stem cell differentiation while opening the possibility to retrieve specific colonies from the culture dish for downstream analysis.